Integrating Islamic Values into Art Practice: Prophetic Education at ISI Surakarta - Kardiyanto, Wawan (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2025)
This study aims to determine and analyze how the strategies and implications are applied in prophetic education by building spiritual and ethical awareness of students at ISI Surakarta. This study used qualitative methods with a phenomenological approach. The data collection technique involved interviews with informants, namely first-semester students at ISI Surakarta. Observations and documentation were conducted to supplement the required data. The resulting data were then analyzed and reduced to produce meaningful research conclusions. This finding highlights that applied prophetic education implications can build spiritual and ethical awareness of students. Spiritual and ethical awareness are seen in the process of student work by integrating Islamic teachings in the verses of the Quran that inspire the results of student artwork. Students view the work as a medium for cultural da'wah and conveying moral messages, such as in religious music works created by students themselves under the direction of lecturers. In addition, the Karawitan song art performance with a religious theme. All departments that receive PAI material are not exempt from the application of prophetic education. The strategy for developing students' spiritual and ethical awareness is carried out through the integration of prophetic values in Islamic Religious Education learning that is in line with the artistic context and institutional goals, strengthening spirituality in the learning process, and implementing creative tasks such as creating lyrics and works of art inspired by verses from the Qur'an in various art study programs.